1999
DOI: 10.1139/h99-028
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Responses to Maternal Strength Conditioning Exercises in Late Gestation

Abstract: Cardiovascular responses to strength conditioning exercises were examined in 12 healthy pregnant women and their unborn fetuses during the third trimester. A group of 12 healthy nonpregnant women of similar ages, parity, body height, and pre-pregnant body mass was also studied. Maternal heart rate and blood pressure and fetal heart rate (FHR) responses were measured in both the supine (30 degrees tilt) and seated postures during handgrip (HG), single-leg extension (SL), and double-leg extension (DL) exercise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 19 publications
4
39
0
5
Order By: Relevance
“…Even with the accumulation of sets and the increase in total exercise time, no FHR alterations were found. These results are similar to those of Avery et al 12 , who tested (n=12, gestational age 31±1 weeks) the performance of bilateral leg extension exercise with 3 sets of 10 repetitions at 50, 70 and 90% of 10-RM and found no significant difference in FHR between all intensities measured.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Even with the accumulation of sets and the increase in total exercise time, no FHR alterations were found. These results are similar to those of Avery et al 12 , who tested (n=12, gestational age 31±1 weeks) the performance of bilateral leg extension exercise with 3 sets of 10 repetitions at 50, 70 and 90% of 10-RM and found no significant difference in FHR between all intensities measured.…”
Section: Discussionsupporting
confidence: 91%
“…As originally hypothesized, the current study demonstrated that FHR was not altered by maternal resistance exercise and during 25 minutes of post-exercise recovery. All fetuses showed a normal response, between 120-160 bpm, indicating that the fetuses did not experience hypoxia and their well-being was not compromised throughout the exercise or during recovery 12,19 . In the present study, one protocol of a single type of exercise was assessed each day the women visited the laboratory, which may indicate that the duration of the muscle contraction was small and did not reflect in the FHR response.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Slediti je treba občutku in telesni kondiciji.7 Znano je, da kratkotrajna submaksimalna vadba pri nosečnici in plodu ne povzroči negativnih odzivov. 41,61 Vadba, ki uporablja manjša bremena, ali na splošno bolj razširjena pod imenom fitnes, je v svetu med nosečnicami zelo razširjena. To je vadba na posebnih napravah, trenažerjih, ki obremenijo točno določeno skupino mišic ali celo posamezno mišico, obenem pa omogočajo zelo natančno določitev intenzivnosti vadbe.…”
Section: Fitnesunclassified
“…A scarce amount of research exists regarding the effects of other training modes, such as resistance training or circuit training during pregnancy, on fetal health and development as well as any continued benefits for the neonate, especially with regards to cardiovascular development and function. Research to date has only determined that various modes of maternal exercise training do not present undue risk to fetal or neonatal development [2,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%